ESTRATÉGIA GAMIFICADA PARA O ENSINO DE EMPREENDEDORISMO: proposta metodológica prática para potencializar a pedagogia empreendedora no ensino superior em São Luís - MA - SANTOS JUNIOR, Verissimo Barros dos (2024)
Entrepreneurship can be understood as creating something or innovating in a process that already exists. There are several definitions of the term. Given so many concepts of entrepreneurship, its importance in society stands out, whether in economic relations in the country and the world or even the supply of basic needs, such as health and education, both of which are provided by companies. The term entrepreneurship is more than just starting a business, the characteristics can be found in professionals who seek to solve problems in a creative way, and it relates to characteristics, which can be developed in people, who open businesses or not. To achieve this, it is essential to include entrepreneurial education in the students' training process, especially in higher education. In this sense, we seek to structure a gamified process for an entrepreneurial training proposal within the Undergraduate Administration course. The study also analyzes the students' experience, focusing on the use of digital technologies in teaching, disseminating and encouraging entrepreneurial training. In addition to raising the characteristics of entrepreneurial education and its impacts on the creation of new businesses and verifying the contributions of Information and Communication Technologies in teaching and training new entrepreneurs. In the present investigation, the population is defined as students of the undergraduate course in Administration at the Federal University of Maranhão - UFMA. Through bibliographic and exploratory research, the concepts surrounding the teaching of entrepreneurship are initially addressed and the potential of gamification in higher education education is presented. In this way, there is a need to consolidate the entrepreneurial culture during the training process, which requires the use of digital resources to stimulate students' ability to think, analyze scenarios and glimpse trends before making any decision to create a new model. of business.